1985
DOI: 10.3146/pnut.12.1.0006
|View full text |Cite
|
Sign up to set email alerts
|

Row Pattern and Weed Management Effects on Peanut Production1

Abstract: Field experiments were conducted from 1981 through 1983 on a Dothan sandy loam (Plinthic Paleudults) at Headland, Alabama, to investigate the effects of row patterns and weed management systems on weed control, peanut yield, and net returns to land and management. Treatments consisted of three row patterns, a) conventional 91-cm rows, b) dual twin 18-cm rows, and c) triple twin 18-cm rows, and six weed management systems ranging from none to various combinations of herbicide and mechanical inputs. The experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…Consistent with other research (Hauser and Buchanan, 1981;Colvin et al, 1985;Yoder et al, 2003), results from these trials indicate that, in addition to decreased incidence ofTSWV, growers will most likely improve weed control when adopting twin row planting patterns compared to single row plantings. However, these results also suggest that use of twin row planting patterns will not eliminate the need for herbicides in peanut.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Consistent with other research (Hauser and Buchanan, 1981;Colvin et al, 1985;Yoder et al, 2003), results from these trials indicate that, in addition to decreased incidence ofTSWV, growers will most likely improve weed control when adopting twin row planting patterns compared to single row plantings. However, these results also suggest that use of twin row planting patterns will not eliminate the need for herbicides in peanut.…”
Section: Resultssupporting
confidence: 78%
“…Hauser and Buchanan (1981) reported improved weed control when peanut was seeded in narrow rows compared with single row planting patterns. Colvin et al (1985) reported more effective control of sicklepod, Florida beggarweed [Desmodium tortuosum (Sw.) DC], and bristly starbur (Acanthospermum hispidum DC) in both twin row and narrow row planting patterns compared with single row planting patterns. However, enhanced weed control in peanut seeded in twin row planting patterns did not reduce herbicide usage when compared with control in single row planting patterns (Colvin et al, 1985).…”
mentioning
confidence: 99%
“…The only variable with an interaction between inoculant and phorate treatments was (Colvin et al, 1985;Hauser and Buchanan, 1981;Wehtje et al, 1984) and soil temperature through shading. Excessive soil temperatures can lead to pollen sterility, reduce flowering and fruit set, and inhibit pegs from entering the soil (Kvien, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…The yield benefits of a twin row planting pattern have been widely researched and published (Wehtje et al, 1984;Colvin et al, 1985;Lanier et al, 2004;Sorensen et al, 2007; ground cover, and improved light interception can be credited for this reported yield advantage. Previous research shows that a portion of the yield increase in twin rows compared to single rows is likely due to the reduction in pressure of common peanut diseases including Tomato spotted wilt Tospovirus (TSWV) (Brown et al, 2005;Tillman et al, 2006;Culbreath et al, 2008) and stem rot, caused by the fungus Sclerotium rolfsii, (Minton and Csinos, 1986, Sorensen et al, 2004;Sconyers et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The yield benefits of a twin row planting pattern have been widely researched and published (Wehtje et al, 1984;Colvin et al, 1985;Lanier et al, 2004;Sorensen et al, 2007;. Research has shown that a myriad of reasons including improved disease control, improved weed suppression, shortened time to full ground cover, and improved light interception can be credited for this reported yield advantage.…”
mentioning
confidence: 99%